2013
DOI: 10.1021/ct300488y
|View full text |Cite
|
Sign up to set email alerts
|

Toward Reproducing Sequence Trends in Phosphorus Chemical Shifts for Nucleic Acids by MD/DFT Calculations

Abstract: This work addresses the question of the ability of the molecular dynamics-density functional theory (MD/DFT) approach to reproduce sequence trend in (31)P chemical shifts (δP) in the backbone of nucleic acids. δP for [d(CGCGAATTCGCG)]2, a canonical B-DNA, have been computed using density functional theory calculations on model compounds with geometries cut out of snapshots of classical molecular dynamics (MD) simulations. The values of (31)P chemical shifts for two distinct B-DNA subfamilies BI and BII, δP/BI … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 66 publications
0
46
0
Order By: Relevance
“…A high-quality NMR experiment is available for the A 3 T 3 sequence, providing a very large number of NOE and residual dipolar coupling restraints. 36 For the A 3 T 3 sequence, εζ OL1 refinement resulted in a notable increase of twist for CA/TG steps by more than 3°. This is desirable considering the known underestimation of the twist value in CA steps by the ff99bsc0 force field.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…A high-quality NMR experiment is available for the A 3 T 3 sequence, providing a very large number of NOE and residual dipolar coupling restraints. 36 For the A 3 T 3 sequence, εζ OL1 refinement resulted in a notable increase of twist for CA/TG steps by more than 3°. This is desirable considering the known underestimation of the twist value in CA steps by the ff99bsc0 force field.…”
Section: Resultsmentioning
confidence: 96%
“…However, recent theoretical work of Precechtelova et al has suggested that δP/BI and δP/BII in fact exhibit substantial sequence dependence. 36 Sequence-dependence of δP can arise when the base pair steps differ in their helical geometry and average values of α, ε and ζ torsions. Note that the actual values of the α torsion may influence δP as well.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation of the DNA alone shows that the B‐II state is slightly underpopulated compared to the expectation that most dinucleotides spend ~85% of the time in the B‐I state and roughly 15% of the time in the B‐II state (Perez et al ., ; Schwieters and Clore, ). The difference between the experimentally determined percentage of B‐II states in the simulations here (Table ) and elsewhere (Precechtelova et al ., ; Zgarbova et al ., ) is sufficient to indicate that force field parameterization for backbone dihedrals of nucleic acids is still needed (Zgarbova et al ., ) even with the use of the parmpbsc0 corrections. With that in mind, the conclusion that we draw from the large increase in B‐II states in the complex is that the f‐ImPyIm significantly increases the likelihood that the DNA backbone will adopt the B‐II conformation, which results in a wider minor groove when compared to the B‐I state.…”
Section: Resultsmentioning
confidence: 99%
“…The use of chemical shifts as structural parameters presumes a detailed knowledge of structure–chemical shift relationships for a system and nucleus in question. While our theoretical work in this field so far concentrated on chemical shifts of 31 P in nucleic acids, the study presented in this article was motivated by our preceding experimental investigation of a receiver domain of the sensory histidine kinase CKI1 of Arabidopsis thaliana (CKI1 RD ) . CKI1 is a constitutively active component of the multistep phosphorylation cascade, transducing signal in a form of phosphate transfer from D1050 of CKI1 RD to a histidine residue of its downstream partners, Arabidopsis Histidine Phospotransfer proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Our account of theoretical versus experimental chemical shifts of the β 3 ‐α 3 loop amino acids, I124‐M133, is thus limited to sequence trends in heavy atom chemical shifts for the bound protein. We first test the ability of the MD/DFT approach with the inclusion of explicit solvent to reproduce chemical shift trends in both the free and the coordinated protein. The results are critically compared to previously published and newly obtained experimental data, with the goal of establishing a suitable model size.…”
Section: Introductionmentioning
confidence: 99%